Step
*
1
2
of Lemma
rsum-as-itop
1. n : ℤ
2. m : ℤ
3. x : {n..m-} ⟶ ℝ
4. n < m
5. d : ℤ
6. 0 < d
7. ∀n:ℤ. ∀x:{n..n + (d - 1) + 1-} ⟶ ℝ.  (Π(λx,y. (x + y),r0) n ≤ k < n + (d - 1) + 1. x[k] = Σ{x[k] | n≤k≤n + (d - 1)})
8. n1 : ℤ
9. x1 : {n1..n1 + d + 1-} ⟶ ℝ
⊢ (Π(λx,y. (x + y),r0) n1 ≤ k < (n1 + d + 1) - 1. x1[k] + x1[(n1 + d + 1) - 1]) = Σ{x1[k] | n1≤k≤n1 + d}
BY
{ ((Subst' (n1 + d + 1) - 1 ~ n1 + (d - 1) + 1 0 THENA Auto) THEN (RWO  "rsum-split-last" 0 THENA Auto)) }
1
1. n : ℤ
2. m : ℤ
3. x : {n..m-} ⟶ ℝ
4. n < m
5. d : ℤ
6. 0 < d
7. ∀n:ℤ. ∀x:{n..n + (d - 1) + 1-} ⟶ ℝ.  (Π(λx,y. (x + y),r0) n ≤ k < n + (d - 1) + 1. x[k] = Σ{x[k] | n≤k≤n + (d - 1)})
8. n1 : ℤ
9. x1 : {n1..n1 + d + 1-} ⟶ ℝ
⊢ (Π(λx,y. (x + y),r0) n1 ≤ k < n1 + (d - 1) + 1. x1[k] + x1[n1 + (d - 1) + 1])
= (Σ{x1[k] | n1≤k≤(n1 + d) - 1} + x1[n1 + d])
Latex:
Latex:
1.  n  :  \mBbbZ{}
2.  m  :  \mBbbZ{}
3.  x  :  \{n..m\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}
4.  n  <  m
5.  d  :  \mBbbZ{}
6.  0  <  d
7.  \mforall{}n:\mBbbZ{}.  \mforall{}x:\{n..n  +  (d  -  1)  +  1\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}.
          (\mPi{}(\mlambda{}x,y.  (x  +  y),r0)  n  \mleq{}  k  <  n  +  (d  -  1)  +  1.  x[k]  =  \mSigma{}\{x[k]  |  n\mleq{}k\mleq{}n  +  (d  -  1)\})
8.  n1  :  \mBbbZ{}
9.  x1  :  \{n1..n1  +  d  +  1\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}
\mvdash{}  (\mPi{}(\mlambda{}x,y.  (x  +  y),r0)  n1  \mleq{}  k  <  (n1  +  d  +  1)  -  1.  x1[k]  +  x1[(n1  +  d  +  1)  -  1])  =  \mSigma{}\{x1[k]  |  n1\mleq{}k\mleq{}n1  \000C+  d\}
By
Latex:
((Subst'  (n1  +  d  +  1)  -  1  \msim{}  n1  +  (d  -  1)  +  1  0  THENA  Auto)
  THEN  (RWO    "rsum-split-last"  0  THENA  Auto)
  )
Home
Index